Multiparametric optimization of coverage for access network - Grimaila, Vitas; Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2004)
An important part of the telecommunication network is subscriber access. The multiparametric method that was developed for the access sector optimization allows choosing the optimal access structure and the technology in respect to the costs with assurance of sufficient quality of service.
Keywords: multiparametric; optimization; access network; broadband